Devon, Its Moorlands, Streams and Coasts - Northcote, Rosalind, 1873-1950; Widgery, F. J. (Frederick John), 1861-1942 (Salt Lake City, UT : Project Gutenberg, 2007)
"Devon, Its Moorlands, Streams and Coasts" by Lady Rosalind Northcote is a geographical and historical account written in the early 20th century. The work delves into the landscapes, towns, and historical events that define the region of Devon, highlighting its scenic beauty and rich heritage. It is likely aimed at readers interested in travel, local history, and the natural environment of the West Country. At the start of the book, the author expresses the difficulty of capturing the essence of Devon in written form, highlighting its varied landscapes and historical significance. The introductory chapters focus on Exeter, described as a "Mother City," emphasizing its deep historical roots and cultural connections to the people of Devon. Through references to local legends and notable events, Northcote evokes a sense of pride and nostalgia while outlining Exeter's role in the larger narrative of English history, showcasing its evolution through different eras, from Roman times to the Civil War. (This is an automatically generated summary.)
Release date is 2007-09-01
E-text prepared by Dave Morgan, Janet Blenkinship, and the Project Gutenberg Online Distributed Proofreading Team
Keywords: Devon (England)